2010
DOI: 10.1111/j.1472-765x.2010.02907.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of clinically relevant fungal species from solid waste and environment of dental health services

Abstract: Aims:  This study was undertaken to detect, identify and determine antifungal susceptibility of yeast strains isolated from dental solid waste and to evaluate airborne fungi in the Brazilian dental health care environment and in the waste storage room. Methods and Results:  A group of 17 yeast strains were identified by macroscopic and microscopic characteristics, API 20C Aux system and Multiplex PCR. All 104 airborne fungal colonies were identified by macroscopic and microscopic morphology. The CLSI broth mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…There are some studies focusing on hospital and dental waste, although very few discuss specific aspects such as their potential biological risks, specially their fungi content. Previous results of our group (Vieira et al., , ) and other studies (Madsen, Alwan, Ørberg, Uhrbrand, & Jørgensen, ) proved the presence of different species of viable bacteria and also of some yeast inside biomedical waste. To widen the discussion on the possible risks to waste workers, this study proposed to investigate fungal strains recovered from dental waste, comparing with those samples isolated from waste workers' tissues (hands and nasal mucosa) and their work wear.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…There are some studies focusing on hospital and dental waste, although very few discuss specific aspects such as their potential biological risks, specially their fungi content. Previous results of our group (Vieira et al., , ) and other studies (Madsen, Alwan, Ørberg, Uhrbrand, & Jørgensen, ) proved the presence of different species of viable bacteria and also of some yeast inside biomedical waste. To widen the discussion on the possible risks to waste workers, this study proposed to investigate fungal strains recovered from dental waste, comparing with those samples isolated from waste workers' tissues (hands and nasal mucosa) and their work wear.…”
Section: Introductionsupporting
confidence: 67%
“…All of these species were previously recovered from dental solid waste by Vieira et al. () except for C. victoriae and O. polymorpha . Górny and Dutkiewicz () reported that yeast are frequently isolated from aerosols in indoor environments including health care settings.…”
Section: Resultsmentioning
confidence: 99%
“…These wastes may be exposed to contamination during the storage period that precedes the final treatment. Vieira et al (2010) evaluated airborne fungi in the Brazilian dental healthcare environment and in the waste storage room. A total of 104 fungal isolates were recovered, 69 % from the waste storage room and 31 % from the clinical/surgical environment.…”
Section: Fungi In Clinical Wastesmentioning
confidence: 99%
“…The survival of pathogens in the clinical wastes and environment has been reported by many investigators in the literature [10][11][12]. Therefore, several technologies including autoclave, irradiation, microwave and chemical disinfection have investigated for the inactivation of these pathogens in clinical wastes [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%